Expressive Voting vs. Self-Serving Ignorance - Katharina Momsen; Markus Ohndorf (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
We experimentally examine the effect of self-serving information avoidance on democratic and individual decisions in the context of climate change mitigation. Subjects need to choose between two allocations which differ in own payoffs and contributions to carbon offsets. In a between-subjects design, we vary the observability of the offset contribution, as well as the institutional decision context: individual consumption, dictatorship, and majority voting in small and large groups. If information is directly observable, we find robust evidence for expressive voting. However, in cases where information is initially unobservable but revealable without cost, there is no significant difference in selfish decisions between institutional decision contexts. We also find robust evidence for the exploitation of moral wiggle room via self-serving information avoidance in our consumption context, as well as with voting in large groups. Our results indicate that information avoidance effectively substitutes expressive ethical voting as an instrument to manage self-image on the part of the voter. This suggests that moral biases might be less likely in elections than previously thought.
Keywords: C90; D12; D64; D72; D89; Q50; 330; Expressive voting; information avoidance; experiment; moral wiggle room; climate change